Enterprises' effectiveness: A study on structure, focus, and enterprises' outcomes - Zlatković-Radaković Matea (Anali Ekonomskog fakulteta u Subotici)
To obtain and retain high performances enterprises are affected by various constituencies's' needs and expectations which are important part of their organizational operationalization. The research goal is to validate the psychometric properties of a widely used holistic view of enterprises performance defined by competing value framework in context of enterprises in transition economy such as Republika Srpska, Bosnia and Herzegovina. To fulfil the aim of the research, a quantitative, research design based on cross-section data was carried out to collect and analyses data from 224 organizational representatives. Covariance-based structural equations modeling was used to test the competing values approach and, if needed, to modify a measurement scale that identifies the extent to which sampled enterprises use the measurement criteria of each aspect of effectiveness to validate the effectiveness of enterprises. All models of effectiveness have acceptable reliability and convergent validity, and discriminant validity of each model was established. Model fit measures indicate acceptable goodness-of-fit. Academics and managers may consider using these measures of effectiveness to better understand the performance/effectiveness phenomenon and have better insight into possibilities for enhancement of different aspects of effectiveness. This study represents the first attempt to investigate and validate the presence of mutual dependence of certain aspects of effectiveness based on a competing values approach in a specific research context.